Sarcopenia Associated with Chronic Obstructive Pulmonary Disease - Kim, Sang Hun (J Bone Metab, 2019)
Sarcopenia is frequently associated with chronic diseases such as chronic obstructive pulmonary disease (COPD) and cancer. COPD, which is characterized by an irreversible airflow limitation, exacerbates respiratory distress as the disease progresses. The prevalence of sarcopenia in stable COPD was reported to be 15% to 25% in previous foreign studies and 25% in a Korean study. As the amount of activity decreases, muscle mass decreases and eventually oxygen cannot be used effectively, resulting in a vicious cycle of deterioration of exercise capacity. Deconditioning due to decreased activity is a major cause of limb muscle dysfunction in patients with COPD. In these patients, the factors that decrease muscle strength and endurance include chronic inflammation, oxidative stress, inactivity, hypoxemia, hormone abnormality, deficits of nutrients such as protein and vitamin D, and the use of systemic corticosteroid. Therefore, treatment and management should either inhibit this process or should be directed toward supplementing the deficiency, such as with exercise, nutritional support, and medications and supplements. The relationship between sarcopenia and COPD is increasingly being reported, with some overlap in clinical features and treatments. We are fascinated to be able to diagnose 2 diseases through similar physical performance tests and to improve both diseases using the same treatment such as exercise. Therefore, this review summarizes the clinical relevance and integrative management of the 2 diseases.